197: Implementing Best Practices for Vaccination Pain Management. Issue 6 (1st June 2014) - Taddio, A; Ipp, M; Apppleton, M; Chambers, C; Halperin, S; Lockett, D; MacDonald, N; Mousmanis, P; Ridell, R Pillai; Rieder, M; Scott, J; Shah, V
Abstract: BACKGROUND: Little attention has been paid to minimizing pain during childhood vaccination which is the most frequent adverse event following immunization. This lack of pain management exposes children to unnecessary suffering and the potential for long-term consequences, such as needle fears and healthcare avoidance behaviours. Vaccination pain negatively affects parents, nurses and physicians as well; all are uncomfortable seeing children being vaccinated and may be non-compliant with immunization schedules in an attempt to reduce the burden of pain. To address this important care gap between what we know about pain and pain management during vaccine injections and what we do, an inter-disciplinary team, Help ELiminate Pain in KIDS Team (HELPinKIDS) was convened in 2008. OBJECTIVES: Identify relevant stakeholders involved in childhood vaccination. Increase awareness of the need to manage pain. Produce knowledge syntheses of evidence-based pain management interventions. Develop a national clinical practice guideline. Develop educational tools (videos and pamphlets) for clinicians and parents. Integrate information about pain in national immunization education and processes of care. Measure impact on health care delivery. DESIGN/METHODS: A mixed methods approach was used: Focus group interviews Individual interviews Quantitative surveys Systematic reviews Guideline creation Observational studies Randomized trials RESULTS: HELPinKIDS has provided evidence-based knowledge synthesis and practice tools (a clinical practice guideline (CPG) and educational videos and pamphlets) to assist in the development of national and regional immunization policies and education. Outcomes that reflect the implementation of best practices for vaccine pain management include: 1. 60% increase in utilization of new analgesic strategies by public health nurse immunizers (49.8% at baseline vs. 77.6% post-CPG implementation: n=2239). 2. 60% increase in utilization of new analgesic strategies by parents after reading pamphlet (10% control vs. 16% intervention: n=436). 3. 100% increase in utilization of any of the most effective analgesic strategies (breastfeeding, topical anesthetics, or sugar water) by parents after education in prenatal class (17% control vs. 34% intervention: n=174). 4. 5% increase in H1N1 vaccination by hospital employees after provision of analgesia (n=392). CONCLUSIONS: HELPinKIDS has had a measurable impact on what we know about pain and the implementation of pain management during vaccine injections and will expand a wide-reaching and comprehensive knowledge translation strategy to continue to address these issues.